Blood pressure is elevated in the absence of resistance artery dysfunction in a mouse model of diet-induced obesity - Lidington, Darcy; Dinh, Danny D.; Chen, Nan; Zhang, Hangjun; Zhou, Yu-Qing; Heximer, Scott P.; Winer, Daniel A.; Martchenko, Alexandre; Bolz, Steffen-Sebastian (Frontiers in Physiology, 2025)
IntroductionHypertension and impaired tissue perfusion are frequent comorbidities in obesity. Since resistance arteries are the primary regulators of peripheral resistance and hence, systemic blood pressure and local blood flow control, we hypothesized that resistance arteries isolated from obese mice would display augmented myogenic reactivity and altered vasomotor responses, compared to non-obese controls. MethodsEight-week-old C57BL/6J mice were fed either a high-fat diet (60% calories from fat; HFD) or a matched control diet for 16 weeks. Body weight, fasting blood glucose, oral glucose tolerance and insulin tolerance were measured. In parallel studies, we measured mean arterial pressure, conducted echocardiographic measurements of cardiac morphology and function and assessed skeletal muscle, mesenteric and cerebral resistance artery reactivity ex vivo with pressure myography. ResultsHFD mice exhibited substantial weight gain and metabolic dysfunction compared to controls. Left ventricular wall thickness and mass were increased in HFD mice, but no other morphological or functional cardiac parameters were different from controls. Blood pressure was modestly increased in HFD mice (from 81 to 87 mmHg; measured under anesthesia); however, contrary to our hypothesis, resistance arteries from HFD mice showed no overt microvascular phenotype in any microvascular bed tested (i.e., no differences in passive diameter, myogenic reactivity or vasomotor responses to phenylephrine or acetylcholine). ConclusionWe conclude that resistance artery function is unaltered in this diet-induced model of obesity with metabolic dysfunction.